The Right to Cultural Heritage: Legal Protection for Indonesia’s Indigenous Art and Traditions Amidst Tourism Growth (Indonesian Tourism Justice Review, 2025)
As tourism flourishes in Indonesia, the protection of indigenous cultural heritage faces mounting challenges. This paper explores the legal frameworks that govern the protection of indigenous art and traditions amidst the pressures of tourism development. Focusing on regions such as Bali, Papua, and Sulawesi, the study analyzes the effectiveness of existing laws aimed at safeguarding cultural heritage, including intellectual property rights and cultural preservation acts. Through a comparative analysis of legal mechanisms, the paper identifies the gaps and weaknesses in the current system, particularly in the face of commercialization and commodification of indigenous cultural practices for tourism purposes. Drawing on interviews with cultural activists, policymakers, and indigenous leaders, the paper argues for stronger legal protections and policies that empower indigenous communities to maintain control over their cultural heritage. The study also proposes innovative solutions such as community-led cultural preservation projects and the implementation of ethical tourism practices that respect indigenous rights. The paper concludes by emphasizing the need for a legal and cultural paradigm shift that prioritizes cultural integrity and sustainability in the tourism sector.